(untitled) (African Journal of Biomedical Research, 2024)
There is insufficient literature on the musculoskeletal related disorders among electrical employees in South-East, Nigeria. This study aimed to investigate the prevalence and pattern of distribution of musculoskeletal disorders among electrical employees in south-east, Nigeria. Socio-demographic characteristics, job background, prevalence and pattern of MSDs of 109 electrical employees (19-57 years) were investigated using a standard Nordic questionnaire. The data collected was analysed using statistical package for social science (SPSS) version 20. Results of the study revealed a high rate of MSD among electrical employees (88.1%). The most affected regions were neck (55.0%), followed by the lower back and shoulders (51.4% each), then the upper back (46.8%), wrists/hands (44.0%), Knees (36.7%), hips/thighs and ankles/feet (33.0% each), the elbow (29.4%). There was a significant relationship between the prevalence of musculoskeletal related disorders and the highest educational status of the electrical employees. A high prevalence of musculoskeletal disorders exists among electrical employees. Trainings on correct ergonomic practices is recommended to be carried out in this population.